The Growth of Islamic Banks and Increase Its Identity through Institutional Approach - Hossain, Shamim; Kiumarsi, Shaian; Jansri, Wilawan (Journal of Entrepreneurship, Business and Economics; Vol 7 No 2s (2019): Special Issue: Contemporary Business Issues in Malaysia: How does this “Tiger Cub” feel today?, 2019)
This study aims to review prior literature on growth of Islamic banks in Bangladesh (IBB) to explain and analyse the role of institutional theoretical approach systematically. This research examines how the growing level of IBB requirements are fulfilled and maintained throughout the banking structure in society. The present study uses a single-case research method and uses semi-structured interviews as the primary data collection. It considers the perspectives of various stakeholder groups in the IBB. In all, 40 participants have participated in this study. In this research, normative aspects of assign institutional theory (IT) are taken into considerations. They vary in their institutional performance and thus have different levels of bias and efficiency. Researchers, therefore, attempt to outline various inadequate information resulting from the common setup in which both incumbents’ structure and banking practices rely on their IT mechanism. The study addresses the structure of the IBB and explains its identity approach, which is one of the important stakeholders. This research proposes a balanced and dominated model of banking practices as a potential solution which increases the institutional identity. This research paper significantly contributes to research on Islamic banking business practices, IT in IBB and banks stakeholders gives a better understanding of the whole growth and identity. Research paper  Keywords: Islamic banks, Identity, Structure, Institutional theory, Bangladesh Reference to this paper should be made as follows: Hossain, S., Kiumarsi, S., & Jansri, W. (2019). The Growth of Islamic Banks and Increase Its Identity through Institutional Approach, Journal of Entrepreneurship, Business and Economics , 7 (2s), 106–143.